Separation of a Plasminogen Activator from Plasminogen or Plasmin in Guinea-Pig Serum by Means of Cationic Agents - Olesen, E. S (Thrombosis and Haemostasis, 1961)
The fibrinolytic activity of the precipitates produced in guinea-pig serum by means of the cationic detergent cetyl pyridinium chloride (germidin®) or by protamine sulphate depends on pH and on the concentration of NaCl during precipitation.By selecting appropriate conditions it is possible to prepare precipitates with considerable fibrinolytic activity on normal fibrin, but without any demonstrable protease activity on heated fibrin. The experimental data indicate that this result is caused by separation of an activator of plasminogen from plasmin and/or plasminogen. This concept implies that the activator and the protease are separate entities.